Actividad ovárica y prolificidad de cabras sincronizadas con progestágenos y suplementadas con propionato de calcio: Ovarian activity and prolificity of goats synchronized with progestages and supplemented with calcium propionate - Flores-Santiago, Ever del Jesus; Sosa-Montes, Eliseo; Alejos-de la Fuente, José Isidro; Germán-Alarcón, Carlos Guillermo; Hernández-Marín, José Antonio; Cadena-Villegas, Said (Ecosistemas y Recursos Agropecuarios, 2021)
The influence of live weight, energy intake on fertility of animals and the benefits of supplying calcium propionate (CP) as a blood glucose precursor have been known for some years. Therefore, in order to determine the response of goats synchronized with progestogens and supplemented with CP, 25 goats were used which were randomly assigned to two experimental treatments: Control (T1, n= 13) drinking 60 mL of water without CP and (T2, n = 12) take 20 g of CP diluted in 60 mL of water. The CP was administered daily during the synchronization of estrus (9 d), which was performed with intravaginal sponges impregnated with chronolone, 250 mg of cloprostenol and 300 IU of eCG; insemination was by laparoscopy, 52 h after removing the sponges. The response to estrus, onset of estrus, percentage of gestation and parturition, prolificacy, blood glucose concentration, and number and size of ovarian follicles were evaluated. Differences (P